Analysis of Completeness and Contextual Aspects of LKPD Physics Based on PBL Vector to Improve Critical Thinking Skills - Herlia, Naziroh Faiqohtul; Wardhany, Merry Khanza Kusuma; Adilah, Bilqis; Rahmawati, Elsa Dwi; Ilmi, Lya Himmatul; Umam, Muhammad Khairul; Subiki, Subiki; Mahardika, I Ketut (Institut Teknologi Pendidikan Indonesia, 2023)
LKPD is a printed media or teaching material containing guide actors that can be used by students to develop their abilities.LKPD is one of the media to create a better learning atmosphere. LKPD was developed based on the PBL (ProblemBased Learning) model which is a learning approach to challenge students to think critically and acquire real-world problem-solving skills. This study was to analyze the completeness and contextual aspects of vector material PBL-based physics worksheets. This research uses the method of Research and Development (R&D).This development research is used to produce certain products and test the effectiveness of these products. The steps in the LKPD development stage include an assessment by development test experts, evaluation, and responses from experts and students. Based on the validation results obtained from the first validator and the second validator, it can be seen that the completeness and contextual aspects of PBL-based Physics Worksheets in vector material obtain an average value of 3 and 4 indicating that the results obtained are good. In addition, the contextual aspects of LKPD are able to improve high-level critical thinking skills in class X high school students because the material presented is related to everyday life. Overall, PBL-based physics worksheets on this vector material were deemed fit to be used as an effective physics learning medium.